1997
DOI: 10.1128/mcb.17.2.862
|View full text |Cite
|
Sign up to set email alerts
|

Nf1-Deficient Mouse Schwann Cells Are Angiogenic and Invasive and Can Be Induced To Hyperproliferate: Reversion of Some Phenotypes by an Inhibitor of Farnesyl Protein Transferase

Abstract: We have developed a potential model of Schwann cell tumor formation in neurofibromatosis type 1 (NF1). We show that mouse Schwann cells heterozygous or null at Nf1 display angiogenic and invasive properties, mimicking the behavior of Schwann cells from human neurofibromas. Mutations at Nf1 are insufficient to promote Schwann cell hyperplasia. Here we show that Schwann cell hyperplasia can be induced by protein kinase A activation in mutant cells. Removal of serum from the culture medium also stimulates hyperpl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
120
1

Year Published

1998
1998
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 136 publications
(135 citation statements)
references
References 61 publications
14
120
1
Order By: Relevance
“…In accordance with several studies in other cell systems (Haklai et al, 1998;Kim et al, 1997;Nagase et al, 1996), treatment of the IBEC with Rasinhibitors inhibited FGF-2 induced cell proliferation. Our data suggest an obligatory signaling cascade to IBEC proliferation that starts with FGFR-1 activation, phosphorylation of the adaptor proteins Shc and FRS2 and subsequent activation of Ras followed by the linear Raf1/MEK/MAPK pathway.…”
Section: Discussionsupporting
confidence: 90%
“…In accordance with several studies in other cell systems (Haklai et al, 1998;Kim et al, 1997;Nagase et al, 1996), treatment of the IBEC with Rasinhibitors inhibited FGF-2 induced cell proliferation. Our data suggest an obligatory signaling cascade to IBEC proliferation that starts with FGFR-1 activation, phosphorylation of the adaptor proteins Shc and FRS2 and subsequent activation of Ras followed by the linear Raf1/MEK/MAPK pathway.…”
Section: Discussionsupporting
confidence: 90%
“…Cells were grown in the presence and absence of either drug for 48 h then assayed for cell proliferation and invasion as described above. We found that both drugs signi®cantly inhibited NID cell [ 3 H]thymidine incorporation ( Figure 6a) and cell invasion ( Figure 6b) at concentrations previously shown to block Ras processing (Kim et al, 1997b) and Src kinase activity (Sobko et al, 1998) in Schwann cells. Both drugs inhibited cell invasion to a similar degree, while herbimycin A also inhibited cell motility as indicated by the small number of cells that reached the bottom of the ®lter (Figure 6b).…”
Section: The Phenotype Of Nid Cells Is Reversed By Inhibitors Of Ras mentioning
confidence: 64%
“…While herbimycin A and L-739,749 may a ect additional signaling molecules, they were used at concentrations previously shown to block Src kinase activity and Ras farnesylation (which is required for Ras to become active), respectively, in Schwann cells (Sobko et al, 1998;Kim et al, 1997b). Both drugs were e ective in reversing the ability of NID cells to invade matrix and to proliferate in the absence of added growth factors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations